Patterns and predictors of fatigue following living donor nephrectomy: Findings from the KDOC Study. Issue 1 (23rd July 2019) - Rodrigue, James R.; Fleishman, Aaron; Schold, Jesse D.; Morrissey, Paul; Whiting, James; Vella, John; Kayler, Liise K.; Katz, Daniel A.; Jones, Jody; Kaplan, Bruce; Pavlakis, Martha; Mandelbrot, Didier A.; et al.
Abstract : This study sought to identify the prevalence, pattern, and predictors of clinical fatigue in 193 living kidney donors (LKDs) and 20 healthy controls (HCs) assessed at predonation and 1, 6, 12, and 24 months postdonation. Relative to HCs, LKDs had significantly higher fatigue severity ( P  = .01), interference ( P  = .03), frequency ( P  = .002), and intensity ( P  = .01), and lower vitality ( P  < .001), at 1‐month postdonation. Using published criteria, significantly more LKDs experienced clinical fatigue at 1 month postdonation, compared to HCs, on both the Fatigue Symptom Inventory (60% vs. 37%, P  < .001) and SF‐36 Vitality scale (67% vs. 16%, P  < .001). No differences in fatigue scores or clinical prevalence were observed at other time points. Nearly half (47%) reported persistent clinical fatigue from 1 to 6 months postdonation. Multivariable analyses demonstrated that LKDs presenting for evaluation with a history of affective disorder and low vitality, those with clinical mood disturbance and anxiety about future kidney failure after donation, and those with less physical activity engagement were at highest risk for persistent clinical fatigue 6 months postdonation. Findings confirm inclusion of fatigue risk in existing OPTN informed consent requirements, have important clinical implications in the care of LKDs, and underscore the need for further scientific examination in this population. Abstract : In this multicenter, prospective analysis of living kidney donors, the authors found that donors had significantly higher fatigue severity and lower vitality compared to healthy nondonors at 1 month postdonation but not at 6, 12, or 24 months postdonation.